The Myth of Forgiveness for Christians in the Gospel Johannes 19:29 and the Gospel John 19:30 (Roland Barthes Semiotic Frame) - Simorangkir, Imelda (PT FORMOSA CENDEKIA GLOBAL, 2025)
The importance of Jesus as a holy figure, as well as the anguish and controversy that surrounded his death, have motivated us to conduct an interdisciplinary investigation of the events surrounding his crucifixion. As a result, this study will look at the crucifixion and death of Jesus through the linguistic. This research is to examine many signs contained in the Gospel of John 19:29 and the Gospel of John 19:30. This research will look at sour grapes as a signifier and sponge as a signified. Aside from that, the researchers would like to look into the hidden meaning or myth in the words